Effect of mechanical separation process on lipid oxidation in European aquacultured sea bass, gilthead sea bream, and rainbow trout products. (September 2016) - Secci, Giulia; Borgogno, Monica; Lupi, Paola; Rossi, Silvia; Paci, Gisella; Mancini, Simone; Bonelli, Antonio; Parisi, Giuliana
Abstract: Mechanical separation systems are a good option to create new fish products and open new market, however studies on the effect on quality of mechanical treatment on species of interest for European aquaculture, such as European sea bass, gilthead sea bream, and rainbow trout are scarce. Thus in this research, the effect on colour, nutritional quality, and lipid stability was considered immediately after separation process and after 90 days of frozen storage. Results revealed that mechanical separation technique significantly affected colour and lipid stability of the three studied species. Increases in L* and secondary oxidation products were observed, together with a decrease of antioxidant capacity. Nutritional value instead was unaffected by treatment. Thus, mechanical separation process could represent a new way to better exploit species of interest for European aquaculture and acquire new market niches, but oxidative processes during the treatment have to be limited and kept under control. Highlights: Mechanical separation system were tested on sea bass, sea bream, and rainbow trout. Mechanical separation system decreased antioxidant capacity. Mechanical separation system increased oxidative processes. Using no marketable fish instead of waste result in high nutritional quality MSM.